2011
DOI: 10.1093/humrep/der126
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial receptivity is affected in women with high circulating progesterone levels at the end of the follicular phase: a functional genomics analysis

Abstract: Our results reveal that elevated progesterone levels on the day of rCG administration can induce significant alterations in the gene expression profile of the endometrium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
177
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 302 publications
(188 citation statements)
references
References 61 publications
6
177
0
5
Order By: Relevance
“…While several studies reported lower pregnancy rates in patients with high progesterone concentration on the day of human chorionic gonadotropin (hCG) administration [1–9], one found a favourable effect on pregnancy outcome [10] and others failed to demonstrate any association [1121]. Although the mechanism by which premature serum progesterone elevation might alter the embryo transfer outcome is still unclear, there are accumulated data suggesting a negative impact on endometrium [22, 23]. Elevated progesterone levels might induce premature endometrial maturation and, as a consequence, earlier opening of the implantation window that leads to asynchronization of the crosstalk between embryo and endometrium.…”
Section: Introductionmentioning
confidence: 99%
“…While several studies reported lower pregnancy rates in patients with high progesterone concentration on the day of human chorionic gonadotropin (hCG) administration [1–9], one found a favourable effect on pregnancy outcome [10] and others failed to demonstrate any association [1121]. Although the mechanism by which premature serum progesterone elevation might alter the embryo transfer outcome is still unclear, there are accumulated data suggesting a negative impact on endometrium [22, 23]. Elevated progesterone levels might induce premature endometrial maturation and, as a consequence, earlier opening of the implantation window that leads to asynchronization of the crosstalk between embryo and endometrium.…”
Section: Introductionmentioning
confidence: 99%
“…The histological dating results by Noyes' criteria in GnRH analogue IVF cycles were confirmed at the molecular level in a study in which advanced endometrial maturation exceeding 3 days was shown in a separate molecular cluster profile [30]. In a recent functional genomics analysis it was revealed that elevated P levels on the day of rhCG can induce significant alterations in the gene expression profile of the endometrium [31].…”
Section: The Effects Of Increased Progesteronementioning
confidence: 87%
“…Кроме этого, ин-дукция роста фолликулов часто сопряжена с измене-нием рецепторного статуса эндометрия, характери-зующегося снижением плотности рецепторов эстра-диола, и увеличением экспрессии рецепторов проге-стерона по сравнению с натуральными циклами [17]. Предполагается, что повышение концентрации про-гестерона оказывает влияние на ряд генов клеток эн-дометрия, вовлеченных в процессы адгезии и нида-ции раннего эмбриона [18]. Однако и этот аспект пока остается дискуссионным.…”
unclassified
“…Во-вторых, очень немногие исследования во-обще оценивали влияние концентрации прогесте-рона в сыворотке крови на морфологическое строе-ние, а тем более профили экспрессии генов эндоме-трия во время «окна имплантации» [18,22]. R. Li и соавт.…”
unclassified
See 1 more Smart Citation